He Kāhui Waiora: Living Standards Framework and He Ara Waiora. COVID-19: Impacts on Wellbeing - Diana Cook; Phil Evans; Hana Ihaka-McLeod; Kara Nepe-Apatu; Jez Tavita; Tim Hughes (New Zealand Government, The Treasury, 2020)
The COVID-19 pandemic is having major impacts on our lives in ways that go far beyond health, extending across all dimensions of wellbeing and all population groups. This paper presents the results of a 'rapid evidence review' of the potential impacts of COVID-19, and the associated economic recession, on the wellbeing of New Zealanders. The analysis identifies potential wellbeing impacts based on experiences of previous pandemics and recessions, as well as emerging data on and insights into the COVID-19 impacts.
Keywords: 330; Coronavirus; Lebensstil; Sozialer Indikator; Gesundheitsvorsorge; Konjunktur; Neuseeland